2018
DOI: 10.5964/jspp.v6i2.859
|View full text |Cite
|
Sign up to set email alerts
|

Self-censorship orientation: Scale development, correlates and outcomes

Abstract: Self-censorship is defined as intentionally and voluntarily withholding information from others in absence of formal obstacles. We conducted cross-sectional and longitudinal research to develop a quantitative measure of individuals’ Self-Censorship Orientation (SCO) and investigated its correlates and outcomes in the context of the intractable Israeli-Palestinian conflict. Stage 1 investigated the factor structure of the scale and its convergent and discriminant validity in a representative sample (N = 499). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 60 publications
(68 reference statements)
0
12
0
8
Order By: Relevance
“…This sociopsychological phenomenon falls within the domain of situations in which individuals either intentionally and voluntarily withhold information from other society members even in the absence of formal obstacles or support such withholding of information that may reflect negatively on the society, creating a climate of silence. Support for self‐censorship thus aims to protect the society in conflict by blocking the dissemination of information viewed as harming a society that is threatened by the rival group and is coping with vital challenges in a violent conflict (see Sharvit et al, ). Moreover, it is one of the mechanisms through which conservative political orientations contribute to the maintenance of intergroup conflict (Bar‐Tal, ).…”
Section: Discussionmentioning
confidence: 99%
“…This sociopsychological phenomenon falls within the domain of situations in which individuals either intentionally and voluntarily withhold information from other society members even in the absence of formal obstacles or support such withholding of information that may reflect negatively on the society, creating a climate of silence. Support for self‐censorship thus aims to protect the society in conflict by blocking the dissemination of information viewed as harming a society that is threatened by the rival group and is coping with vital challenges in a violent conflict (see Sharvit et al, ). Moreover, it is one of the mechanisms through which conservative political orientations contribute to the maintenance of intergroup conflict (Bar‐Tal, ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the above, this study seeks to translate, adapt and provide evidence of validity of the measures provided by the Spanish version of the Self-Censorship Orientation (SCO) scale initially developed by Sharvit et al (2018). To do so, we will start with back-translating the scale, then checking its reliability and dimensionality with three samples from different Spanish-speaking countries (i.e., Spain, Colombia and Mexico).…”
Section: Factors Related To Self-censorshipmentioning
confidence: 99%
“…Thus, the study of self-censorship in today's societies, and particularly in Spain and Latin America, where these problems are salient, is vitally important. In consequence, we set out to adapt the Self-Censorship Orientation (SCO) scale (Sharvit et al, 2018) to Spanish and provide evidence of validity of its measures.…”
mentioning
confidence: 99%
“…A series of studies has shown its scope and the conditions for its use, as well as its motivational basis, as for example, Hameiri, Sharvit, Bar-Tal, Shahar, and Halperin (2017) and Sharvit et al (in press). An edited book has illustrated its use in different institutions of society.…”
Section: Phase 5: Founding Learning Communitymentioning
confidence: 99%